2022
DOI: 10.3390/children9071043
|View full text |Cite
|
Sign up to set email alerts
|

Indications for Hospitalization in Children with SARS-CoV-2 Infection during the Omicron Wave in New York City

Abstract: The emergence of the Omicron variant was accompanied by an acute increase in COVID-19 cases and hospitalizations in New York City. An increased incidence of COVID-19-associated croup in children during the Omicron wave has been recognized, suggesting that there may be other changes in clinical symptoms and severity. To better understand clinical outcomes and health care utilization in children infected with SARS-CoV-2 during the Omicron wave, we performed a cross-sectional study in pediatric patients aged ≤18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 21 publications
4
8
0
4
Order By: Relevance
“…In addition, 26% (N = 1591) of children and adolescents with confirmed SARS-CoV-2 infections were admitted for reasons unrelated to this infection ( Figure 1 D). Other studies have had similar findings regarding incidentally positively tested patients [ 7 ]. For this reason, cases falling into this category should be excluded from analysis when evaluating the SARS-CoV-2-related burden on hospital systems.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, 26% (N = 1591) of children and adolescents with confirmed SARS-CoV-2 infections were admitted for reasons unrelated to this infection ( Figure 1 D). Other studies have had similar findings regarding incidentally positively tested patients [ 7 ]. For this reason, cases falling into this category should be excluded from analysis when evaluating the SARS-CoV-2-related burden on hospital systems.…”
Section: Discussionsupporting
confidence: 73%
“…Our results were in line with research from the United States, the United Kingdom, and Germany that found a higher percentage of newborns and young children hospitalized with COVID‐19 during the Omicron wave 7–10 . A similar observation was also emphasized in studies in different regions 11–14 . Possible reasons for the increase in hospitalizations in this group may be the increase in the total number of cases due to the higher transmission rate of the Omicron variant and the relaxation of restrictive measures.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, 26% (N=1,591) of children and adolescents with confirmed SARS-CoV-2 infections were admitted for reasons unrelated to this infection (Figure 1D). Other studies have had similar findings regarding incidentally-positive tested patients [7]. For this reason, cases falling into this category should be excluded from analysis when evaluating the SARS-CoV-2-related burden on hospital systems.…”
Section: Discussionmentioning
confidence: 88%